ВИДЫ ВНИМАНИЯ ПРИ РЕДАКТИРОВАНИИ ПОГРЕШНОСТЕЙ В НАУЧНЫХ ТЕКСТАХ (Filološke pripombe, 2019)
The article reviews types of attention during editing errors in scientific text. The strategy of editing correlates with attention dominating in the process of special slow reading. The author distinguishes the following types of attention: wavy, shuttle-like, spasmodic, web-like and spiral.